Strategi Pengembangan UKM Gethuk Pisang Guna Melestarikan Makanan Tradisional - Cahyono, Wahyu Eko; Kunhadi, Dedy (Jurnal Media Teknik dan Sistem Industri, 2020)
Abstract— Small and medium enterprises (SMEs) are business sectors that play an important role as a backbone of a nation or region"s economics. Most problems faced by small and medium enterprises (SMEs) are capital, management and production process. This study aims to give strategic proposals in expanding small and medium enterprises of gethuk pisang for conserving traditional food. The methods used in this research are internal factor evaluation (IFE), external factor evaluation (EFE), and strengths- weaknesses - opportunities - threats (SWOT), so internal factors and external factors that faced by the small and medium enterprises can be identified. Based on SWOT analysis, some analysis strategy can be used to expand the small and medium enterprises of gethuk pisang. Result showed the small and medium enterprises of gethuk pisang were in first quadrant at SWOT cartesian diagram, meant the right strategies were strengths opportunities (SO) or Growth strategy. The strategies that will be used are local government holds traditional food festival, upgrade the quality of the product and use on-line marketing technology. In conclusion, the sales of gethuk pisang products from small and medium enterprises can increase and correlate with income increase, so small and medium enterprises (SMEs) of gethuk pisang can have competitiveness and grow.Keywords— Strategy, Gethuk pisang, IFE, EFE, SWOT.  Abstrak— Usaha kecil dan menengah (UKM) merupakan suatu sektor usaha yang memiliki peran penting sebagai tulang punggung perekonomian suatu negara atau daerah. Sebagian besar permasalahan-permasalahan yang dihadapi UKM adalah permodalan, manajemen, dan proses produksi. Penelitian ini bertujuan untuk memberikan usulan strategi dalam mengembangkan UKM gethuk pisang dalam melestarikan makanan tradisional. Metode yang digunakan dalam penelitian ini adalah Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), dan Strengths–Weaknesses - Opportunities-Threats (SWOT), sehingga dapat diidentifikasi faktor-faktor internal yang dimiliki dan faktor-faktor eksternal yang dihadapi oleh UKM. Berdasarkan analisa SWOT, maka akan diperoleh beberapa alternatif strategi yang dapat digunakan dalam mengembangkan UKM gethuk pisang. Hasil penelitian menunjukkan bahwa UKM gethuk pisang berada di kuadran I pada diagram kartesius SWOT, yang berarti strategi yang tepat digunakan adalah strategi Strengths Opportunities (SO) atau strategi Growth. Strategi-strategi yang akan digunakan adalah: Pemerintah Daerah mengadakan festival makanan tradisional,  mutu produk lebih ditingkatkan, dan memanfaatkan teknologi media pemasaran on-line. Dengan demikian, produk UKM gethuk pisang dapat terjadi peningkatan penjualan dan berkorelasi dengan peningkatan pendapatan, sehingga UKM gethuk pisang memiliki daya saing dan dapat berkembang.Kata kunci — Strategi, Gethuk Pisang, IFE, EFE, SWOT